Formulation of Blush Preparations by Using Natural Coloring from Red Beetroot Extract (Beta vulgaris L.) - Suci Wulan Sari; Ratna Djamil; Faizatun Faizatun (Universitas Gadjah Mada, 2021)
Beetroot (Beta vulgaris L.) has compounds that can be used for body health, beauty skincare, food additives, and much more. This research was aimed to prepare the dry extract of beetroot and formulate it into a loose powder, compact powder, and cream. The preparation was started by adding 2, 4, or 6% of dry extract, then blending the pulp and drying the resultant residue using a freeze dryer. Testing on color homogeneity, polishing, breakage, pH stability, color stability, and the hedonic test was carried out to determine the product quality. The initial result of phytochemical screening showed it might contain flavonoids, alkaloids, saponins, tannins, triterpenoids, steroids, and quinones. The color stability test performed at 30 °C showed that the cream was unstable while other forms showed fair stability at 8 °C. All dosage forms were homogeneous and could be applied easily. The breakage test showed no fractures. The pH remained stable for all formulas (between 3–5) after 28 days of storage. The color stability test showed that the significant discoloration only happened to the loose powder and cream. The hedonic test showed that the compact powder with a concentration of 6% was the most preferred formula by users.